EFEKTIVITAS PENGGUNAAN MODEL PEMBELAJARAN TALKING STICK TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA DI KELAS VIII MTs YPKS PADANGSIDIMPUAN - Nur Amina Pane (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2018)
ABSTRACT This study aims to describe of effectiveness of using talking stick learning model on students’ mathematical communication ability at the eighth grade students of YPKS Padangsidimpuan. The research was conducted by applying experimental method with 25 students as the sample and they were taken by using cluster random sampling technique from 127 students. Observation and test were used in collecting the data. Based on the data analysis, it was found that: (1) the average of using talking stick learning model was 3.67 (very good category) and (2) the average of students’ mathematical communication ability before using talking stick learning model was 44.73 (poor category) and after using talking stick learning model was 80.27 (very good category). Furthermore, based on N-gain formulation, 56% (14 students) showed talking stick learning model was very effective and 44% (11 students) showed talking stick learning model was effective. Keywords: talking stick learning model, mathematical communication ability